2018
DOI: 10.1111/vcp.12598
|View full text |Cite
|
Sign up to set email alerts
|

Rapid multiple immunofluorescent staining for the simultaneous detection of cytokeratin and vimentin in the cytology of canine tumors

Abstract: The RMIF method might be a useful tool for diagnostic cytology in veterinary medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…This finding is in total agreement with an early report on the consistent detection of Vimentin expression in six cell lines explanted from COMM (including Shadow), a skin melanoma‐derived cell line and 28/29 tumour sections prepared from 11 COMM, 14 cutaneous and 4 digital canine melanomas . Vimentin is generally expressed by mesenchymal and neuroectodermal cells in normal tissue, and neoplastic cells that had undergone EMT in a high proportion of canine cancers . Along with Vimentin, tumour sections and primary cell lines consistently expressed biologically active MMP2 as revealed by IF and zymography.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in total agreement with an early report on the consistent detection of Vimentin expression in six cell lines explanted from COMM (including Shadow), a skin melanoma‐derived cell line and 28/29 tumour sections prepared from 11 COMM, 14 cutaneous and 4 digital canine melanomas . Vimentin is generally expressed by mesenchymal and neuroectodermal cells in normal tissue, and neoplastic cells that had undergone EMT in a high proportion of canine cancers . Along with Vimentin, tumour sections and primary cell lines consistently expressed biologically active MMP2 as revealed by IF and zymography.…”
Section: Discussionsupporting
confidence: 91%
“…Since the air-dried and methanol-fixed smears are commonly used for cytology in the veterinary field, methanol was found to be the best fixative for AgNORs. In addition, availability of other fixatives was thought to be meaningful because our recent studies demonstrated that acetone and NBF were optimal fixatives for immunocytochemistry of cytokeratin/vimentin [12] and CD antigens [13], respectively. Since the smear slide used for fluorescence immunocytochemistry can be reused for other stains [12,13], the established AgNOR stain could possibly be utilized in combination with fluorescence immunocytochemistry.…”
mentioning
confidence: 99%
“…Complete blood count and blood chemical analyses, including C-reactive protein levels for dogs, were performed to evaluate the general conditions and concomitant diseases in all these cases. ICC was performed in accordance with the recently published method of the multiple fluorescent ICC (FICC) method [14]. The mouse monoclonal anti-human E-cadherin (clone 36, 1:100; BD Biosciences, Franklin Lakes, NJ, USA) and rabbit monoclonal anti-human vimentin (clone SP20, 1:200 dilution; Spring Bioscience, Pleasanton, CA, USA) were used as primary antibodies and incubated for 15 min at 37 °C.…”
mentioning
confidence: 99%